AMLEORATIVE ROLE OF ESCULETINô€‡§MEDIATED RENOPROTECTION AGAINST GENTAMICINô€‡§INDUCED NEPHROTOXICITY AND POSSIBLE INVOLVEMENT OF Nô€‡§METHYLô€‡§Dô€‡§ASPARTATE RECEPTORS - Bhatia, Alka; Chadha, Rishmeen; Chadha, Rishmeen; Jain, Upendra Kumar; Jain, Upendra Kumar; Singh, Gurpreet; Singh, Gurpreet (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: In this investigation, the amleorative role of esculetin (Esc) was investigated in gentamicin (Genta) nephrotoxicity in rats and the possible role of N-methyl-D-aspartate receptors (NMDAR) in genta-induced nephrotoxicity. Methods: Genta (100 mg/kg/day, i.p. for 7 days) was administered to rats for the induction of nephrotoxicity, and subsequently, the extent of renal damage was measured by estimating creatinine clearance (CrCl), blood urea nitrogen (BUN), uric acid, microprotienuria and fractional excretion of sodium, and potassium. In addition, renal superoxide anion generation (SAG), Thiobarbituric acid reactive substance (TBARS), and reduced glutathione (GSH) level were used to evaluate renal oxidative parameters. Renal myeloperoxidase (MPO) activity was used to measure renal inflammation. D-serine, NMDA agonist was used in this study to evaluate the role of NMDA antagonist in genta-induced nephrotoxicity. Histopathological examination was performed using hematoxylin and eosin staining method. Results: Genta-treated rats exhibited remarkable changes in renal parameters like increase in BUN, uric acid, microprotein fractional excretion of sodium and potassium with decrease in CrCl and similarly biochemical parameters like increase in SAG, thiobarbituric acid reactive species (TBARS), MPO activity with decrease in GSH level. Treatment with Esc (5 and 10 mg/kg/day, i.p for 7 days), NMDAR antagonist attenuated the genta-induced nephrotoxicity but did not shown significant effect on combined use of genta and D-serine treated group. Histopathological examination of gentatreated rats. The coadministration of Esc + genta-protected kidney tissue from nephrotoxic effect of genta as illustrated by normalization of tubules but not with the combined use of Esc + genta + D-serine treated rats. Conclusion: Esc displayed protective effect in genta-induced nephrotoxicity but combined effect of Esc + genta + D-serine abolished the protective effect of Esc thus confirming that NMDAR may be involved in genta-induced nephrotoxicity.